Chigger mites (Trombidiformes: Trombiculidae) of birds from Brazilian southeastern: morphological studies and investigation of the presence of Rickettsia spp. - Silva, Ricardo Bassini (2017)
Brazil has 58 species of chigger mites parasitizing different animal groups. Of these, only 6 species were reported for birds, being 1 of Apolonia, 2 of Eutrombicula, 1 of Neoschoengastia and 2 of Parasecia. The larvae of chiggers cause deep lesions and cutaneous reactions in the host, and are often cited as vectors of pathogens. In the United States, public health departments have come across the need for cataloging and knowledge of the biology of these mites as potential vectors of Rickettsia spp. In Brazil, the first cases of Brazilian Macular Fever (BMF) diagnosed in São Paulo were associated with these mites because they were found in outbreaks of the disease. However, its role in the epidemiology of rickettsial disease has not been confirmed. Another concern is dermatitis caused by the bite of these mites, popularly known as trombiculiasis. As it is well known, thrombiculid mites are not specific and several cases of bites in humans have been reported. Thus, the purpose of the present study is to know the current situation of chigger mites parasitizing birds, to clarify aspects of its taxonomic complexity, as well as to provide information about its participation in the epidemiology of Rickettsia in some localities in the southeastern region of the country. From the material examined in the present study were identified 8 species: Blankaartia shatrovi n. sp., Blankaartia sinnamaryi, Microtrombicula n. sp., Eutrombicula tinami, Eutrombicula goeldii, Parasecia n. sp.1, Parasecia n. sp.2, Parasecia n. sp.3. The mites were kept in absolute alcohol, were submitted to DNA extraction and investigation of the presence of Rickettsia. One of the samples showed 100% for Rickettsia felis. Therefore, for Brazil now, we have 13 species described for the entire national territory, with the exception of the Midwest region, and, in addition, the first record of the presence of Rickettsia in chigger mites on South America.